The Effects of Expectation Inflation on Aggregate Demand: Examining the South African Inflation Expectation Channel of South African Monetary Policy - Ncanywa, T.; Ralarala, O. (Journal of Reviews on Global Economics, 2020)
South Africa targeted inflation since February 2000 as its monetary policy framework to ensure long-run price stability and continues to pursue a target of 3-6% for headline CPI inflation. Monetary policy emphasises the importance of promoting economic growth that can be sustained and maintenance of low inflation in an economy. Therefore, the paper seeks to check whether a relationship between economic growth (GDP) and expectation inflation exists. The autoregressive distributive lag (ARDL) econometric methodology was employed to achieve the objectives. The ARDL bounds test found that there is a long-run cointegration between GDP and expectation inflation. Moreover, the ARDL results revealed that in the long run expected inflation had a negative significant effect on GDP. This implies that lower expectation inflation could stimulate economic growth. It is recommended that South Africa should continue to target inflation because its target band of 3% to 6% keep policy makers on the loop.